You can find the answer on quizzez i promise you
<span>Simplifying
25 + 10(12 + -1x) = 5(2x + -7)
25 + (12 * 10 + -1x * 10) = 5(2x + -7)
25 + (120 + -10x) = 5(2x + -7)
Combine like terms: 25 + 120 = 145
145 + -10x = 5(2x + -7)
Reorder the terms:
145 + -10x = 5(-7 + 2x)
145 + -10x = (-7 * 5 + 2x * 5)
145 + -10x = (-35 + 10x)
Solving
145 + -10x = -35 + 10x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-10x' to each side of the equation.
145 + -10x + -10x = -35 + 10x + -10x
Combine like terms: -10x + -10x = -20x
145 + -20x = -35 + 10x + -10x
Combine like terms: 10x + -10x = 0
145 + -20x = -35 + 0
145 + -20x = -35
Add '-145' to each side of the equation.
145 + -145 + -20x = -35 + -145
Combine like terms: 145 + -145 = 0
0 + -20x = -35 + -145
-20x = -35 + -145
Combine like terms: -35 + -145 = -180
-20x = -180
Divide each side by '-20'.
x = 9
Simplifying
x = 9.
Hope this helps you ! =')</span>
9514 1404 393
Answer:
increasing 7/24 ft per week
Step-by-step explanation:
An expression for the length of the base can be written from the Pythagorean theorem relation between the sides of the triangle.
If the height is 7-x, where x is the number of weeks after the height is 7 feet, then the base length is ...
b = √(25^2 -(7-x)^2) = √(625 -(49 -14x +x^2)) = √(-x^2 +14x +576)
Then the rate of change of b with respect to x is ...
b' = (-2x +14)/(2√(-x^2 +14x +576))
When x=0, the rate of change of the base is ...
b' = 14/(2√576) = 7/24
The base is increasing 7/24 ft per week when the height is 7 ft.